2017
DOI: 10.3892/mmr.2017.7170
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles promote osteogenic differentiation of human periodontal ligament stem cells via the p38 MAPK signaling pathway

Abstract: Gold nanoparticles (AuNPs) are a promising material for use in regenerative medicine due to their biocompatibility and easy functionalization with biomolecules including growth factors, DNA and peptides. In the present study, transmission electron microscopy indicated that the AuNPs were monodisperse and spherical in shape, with an estimated average diameter of 13 nm. And the cellular effects of AuNPs on the osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs) and the associated signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…It has been reported that during the process of adipocyte differentiation, cell morphology will change. With the change of cell morphology, the synthesis and assembly of actin and other major cytoskeleton proteins will also change [33], so the pathways involved in cell growth, proliferation, migration, and differentiation may affect lipid deposition. In fact, classical cell signaling pathways such as the MAPK signaling pathway and citrate cycle (TCA cycle) play an indispensable role in many cell responses, such as cell proliferation and differentiation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that during the process of adipocyte differentiation, cell morphology will change. With the change of cell morphology, the synthesis and assembly of actin and other major cytoskeleton proteins will also change [33], so the pathways involved in cell growth, proliferation, migration, and differentiation may affect lipid deposition. In fact, classical cell signaling pathways such as the MAPK signaling pathway and citrate cycle (TCA cycle) play an indispensable role in many cell responses, such as cell proliferation and differentiation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of osteogenic markers and alizarin red staining were upregulated by 100 nM FICZ. Several signalling pathways were reported to be involved in the study of agents promoting osteogenic differentiation of PDLCs, including JNK, p38 MARK and so on (Niu et al, ; Tang et al, ). Wnt/β‐catenin signalling pathway has been widely investigated in the osteogenesis process, and it was reported to have a crosstalk with AhR signalling in the development of zebrafish embryos (Wincent, Stegeman, & Jonsson, ).…”
Section: Discussionmentioning
confidence: 99%
“…The relative osteogenic gene expression value for control was one in this experiment. Collagen1 (COL1) is the most prominent protein that occurred in the bone matrix and generated during the proliferation of osteoblast cells [42]. The expression of the COL1 gene marker from hMSCs shows the formation of bone cells in the presence of G. frondosa.…”
Section: Mineralization and Real-time Pcr Analysismentioning
confidence: 99%